PENERIMAAN MASYARAKAT TERHADAP VAKSIN BOOSTER COVID-19 DI KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Dewi, Kadek Cantika; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2022)
ABSTRACT The COVID-19 vaccination is currently the focus of efforts to prevent the transmission of COVID-19 in various countries, including Indonesia. The success of the vaccination effort will depend on the level of public acceptance of the vaccination effort. The purpose of this study was to determine public acceptance of the COVID-19 booster vaccine in South Kuta District, Badung Regency. The research design is cross-sectional with the population of South Kuta District. The sample size of 150 people was obtained by voluntary sampling technique. Data were collected through direct interviews using a questionnaire. Data analysis using chi-square test. 96% of COVID-19 booster vaccination receipts have been vaccinated and 4% have not been vaccinated but will receive vaccinations. Most of the COVID-19 booster vaccination receipts were based on self/voluntary encouragement of 64.58%. Higher education level (OR= 1.98, 95% CI 0.93-4.21; p=0.007) was associated with receiving the COVID-19 booster vaccine. Conclusion: 96% of COVID-19 booster vaccination receipts have been vaccinated and 4% have not been vaccinated but will receive vaccination. Most of the COVID-19 booster vaccination receipts were based on self/voluntary encouragement of 64.58%. Higher education level (OR= 1.98, 95% CI 0.93-4.21; p=0.007) was associated with receiving the COVID-19 booster vaccine. There need for optimization of the COVID-19 booster vaccination through the dissemination of information regarding the side effects of the COVID-19 booster vaccine and information regarding access to vaccinations Keyword: COVID-19, vaccine acceptance, Badung